Right to freedom of expression in the light of Quran and Hadith: قرآن وحدیث کی روشنی میں اظہار رائے کی آزادی کا حق - Channar, Dr. Hafiz Mehmood ul Hassan; Ahmed Khan, Prof. Dr. Hafiz Munir; Ahmed Khan, Prof. Dr. Ubaid (Al Khadim Research Journal of Islamic Culture and Civilization, 2022)
Objecting to Islam that it does not give the right to freedom of expression is a complete slander and accusation. Islam has neither put guards on thoughts nor locks on languages, it has allowed the voice of its legitimate rights to be raised everywhere. A religion that can give the right to freedom of religion, how can that religion not give the right to freedom of expression? If the teachings of Islam are studied from the heart, then Islam urges its followers that even in the world, oppression and oppression should be raised against it and oppression should be strictly stopped. It will be explained in the light of Quran and Hadith and this will become clear in this article.